Performance Analysis of LPWAN Using LoRa Technology for IoT Application - Muaz Abdul Rahman, Amir; Hafizhelmi Kamaru Kamaru Zaman, Fadhlan; Afzal Che Abdullah, Syahrul (International Journal of Engineering and Technology, 2018)
This paper was dedicated to study the performance of an Internet of Things (IoT) application using LoRa Wide Area Network (LoRaWAN). LoRa is a Low Power Wide Area Network (LPWAN) technology developed for IoT applications specifically. Due to the facts that LoRa is a new product, there are questions about its reliability. Hence, a conclusive experiment has been made. The experiment conducted to get an insight to LoRa received signal strength (RSSI) and packet loss. The analysis also includes a measurement of the application Signal to Noise Ratio (SNR) between the transmitter and receiver. The results of the experiment show that with a higher spreading factor, LoRa end device provides more immunity against multi-path and signal fading. The proposed IoT application based on this LoRa technology is for autonomous vehicle status information transmission and intervehicle communications, specifically deployed in UiTM Autonomous Vehicle 1 (UiTM AV1).Â Â
Keywords: Internet of Things; LoRa; LPWAN; outdoor; performance analysis.